Historical Mathematical Learning Framework: A Theory-Building Conceptual Model for Advancing Conceptual Understanding, Mathematical Reasoning, and Scientific Literacy - Melis Rosdiani; Yusup Maulana; Angra Meta Ruswana; Nia Kania; Ebenezer Bonyah (International Journal of Contemporary Studies in Education (IJ-CSE), 2026)
Purpose – Although the educational value of the history of mathematics is widely recognized, previous studies have primarily treated it as contextual enrichment rather than as a foundation for learning theory. Consequently, the epistemic processes through which historical mathematical development contributes to contemporary mathematics learning remain insufficiently understood. This study developed the Historical Mathematical Learning Framework (HMLF) as a theory-building conceptual model explaining how the historical evolution of mathematics supports conceptual understanding, mathematical reasoning, and scientific literacy. Methodology – A theory-building conceptual review was conducted through a systematic literature search of Scopus and Google Scholar. Relevant publications were synthesized using iterative conceptual synthesis and constant comparative analysis, focusing on mathematical developments in Ancient India, the Islamic Golden Age, and the Renaissance. Findings – The review identified epistemic reconstruction as the fundamental process underlying the historical evolution of mathematical knowledge. Five interconnected cognitive mechanisms emerged: conceptual abstraction, algorithmic structuring, symbolic generalisation, representational coordination, and evidence-based reasoning. These mechanisms were integrated into HMLF, providing an explanatory framework linking historical epistemic development with constructivism, sociocultural learning, multiple representation theory, and inquiry learning. Novelty – This study introduces epistemic reconstruction as a new theoretical construct, integrates five historically grounded cognitive mechanisms into a unified framework, and proposes HMLF as a theory-building model connecting the historical evolution of mathematics with contemporary learning theory. Significance – HMLF repositions the history of mathematics from contextual enrichment to an epistemic foundation for learning, offering a theoretically grounded basis for curriculum innovation, instructional design, teacher education, and future empirical validation.